Absorbance detector for high performance liquid chromatography based on a deep-UV light-emitting diode at 235 nm - da Silveira Petruci, João Flavio [UNESP]; Liebetanz, Michael G.; Cardoso, Arnaldo Alves [UNESP]; Hauser, Peter C. (Elsevier, 2017)
In this communication, we describe a flow-through optical absorption detector for HPLC using for the first time a deep-UV light-emitting diode with an emission band at 235 nm as light source. The detector is also comprised of a UV-sensitive photodiode positioned to enable measurement of radiation through a flow-through cuvette with round aperture of 1 mm diameter and optical path length of 10 mm, and a second one positioned as reference photodiode; a beam splitter and a power supply. The absorbance was measured and related to the analyte concentration by emulating the Lambert-Beer law with a log-ratio amplifier circuitry. This detector showed noise levels of 0.30 mAU, which is comparable with our previous LED-based detectors employing LEDs at 280 and 255 nm. The detector was coupled to a HPLC system and successfully evaluated for the determination of the anti-diabetic drugs pioglitazone and glimepiride in an isocratic separation and the benzodiazepines flurazepam, oxazepam and clobazam in a gradient elution. Good linearities (r > 0.99), a precision better than 0.85% and limits of detection at sub-ppm levels were achieved.
Keywords: Absorbance detection; Deep-UV; HPLC; Light-emitting diode